SPE Annual Technical Conference and Exhibition, October 5-8, 1997, San Antonio, Texas : proceedings : reservoir engineering - SPE Annual Technical Conference and Exhibition (1997 : San Antonio, Tex.) (San Antonio, Tex. : Society of Petroleum Engineers, 1997)
51